Análise da biocompatibilidade, citotoxicidade e osteocondução do policaprolactona : estudo em ratos - Hirsch, Wâneza Dias Borges (2014)
Bioresorbable polymers have been used as scaffolds in tissue engineering, thus representing an important alternative for reconstruction of lesions and tissue losses. This study aimed to evaluate the in vivo performance of three-dimensional scaffolds made of polycaprolactone (PCL), by means of through a PCL implant on the subcutaneous tissues of rats back and calvaria, as well as the reaction of their kidneys, lungs and liver. The histological analysis of the bone repair process in calvaria showed the presence of newly formed bone growing towards the center of the defects. The formation of a thin fibrous capsule was observed in the tissues adjacent to the scaffold implanted on the back of all animals, with collagenous fibers involving the implant. As for events occurring in animals' kidneys, lungs and liver, there were no harmful tissue alterations in these organs nor the presence of inflammatory process, hyperplasia, metaplasia, dysplasia or hemorrhage. A quantitative analysis of the bone repair process was performed using histomorphometry and cone beam computed tomography (CBCT). Results showed that the newly formed bone grew towards the center of the defects. Statistical analysis revealed that the total area of new bone formation was greater in experimental defects at 21, 60 and 120 days, showing a statistically significant difference. In tomographic analysis found that new bone formation is more likely to occur in experimental defects, but with no statistically significant difference. Considering tomographic analysis as a new method for the assessment of new bone formation, the data obtained from this assessment could not be correlated with those obtained from histomorphometric analysis. Therefore, it can be concluded that PCL scaffolds produced on an additive manufacturing machine are biocompatible, non-cytotoxic and bioresorbable products that promote osteoconduction. PCL showed great potential for clinical use in the treatment of bone defects by increasing bone área and seems to be an appropriate biomaterial to be used in other studies aiming to elucidate issues related to this topic. Additionally, CBCT does not seem to be a useful tool in the evaluation of new bone formation of rat calvaria, which means that histomorphometric analysis is still the most appropriate method.